Structural bioinformatics study of PNP from Schistosoma mansoni - da Silveira, NJF; Uchoa, H. B.; Canduri, F.; Pereira, J. H.; Camera, J. C.; Basso, L. A.; Palma, Mario Sergio [UNESP]; Santos, D. S.; de Azevedo, W. F. (Elsevier B.V., 2004)
The parasite Schistosoma mansoni lacks the de novo pathway for purine biosynthesis and depends on salvage pathways for its purine requirements. Schistosomiasis is endemic in 76 countries and territories and amongst the parasitic diseases ranks second after malaria in terms of social and economic impact and public health importance. The PNP is an attractive target for drug design and it has been submitted to extensive structure-based design. The atomic coordinates of the complex of human PNP with inosine were used as template for starting the modeling of PNP from S. mansoni complexed with inosine. Here we describe the model for the complex SmPNP-inosine and correlate the structure with differences in the affinity for inosine presented by human and S. mansoni PNPs. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: structural bioinformatics; Schistosoma mansoni; PNP; drug design